KETAHANAN PANGAN RUMAH TANGGA PETANI KARET DI KECAMATAN TULANG BAWANG UDIK KABUPATEN TULANG BAWANG BARAT - Lestari, Diana; Lestari, Dyah Aring Hepiana; Sayekti, Wuryaningsih Dwi (Lampung University, 2025)
Rubber is a widely cultivated plantation commodity, but the volatility of rubber prices poses a problem for farmers, as it affects the ability to meet food demands in terms of both quantity and quality. The motivation behind this study was to analyze the level of food security and the quality of household food consumption of rubber farmers in Tulang Bawang Udik Sub district, West Tulang Bawang Regency. This study used survey method with a sample of forty-eight rubber farming households from two villages with land areas of less than one hectare, selected by simple random sampling. Food security was measured by cross-classification between the proportion of food expenditure and the level of household energy consumption. Calculation of household food expenditure was based on a monthly period, while the energy consumption level used the actual energy consumption indicator together with the energy consumption indicators obtained by the recall method. The quality of food consumption patterns was analyzed by determining the PPH score. Computation of the PPH score was acquired by contrasting the genuine AKE score with the standardizing PPH (100). The outcomes show that the results of the cross-classification of energy sufficiency and the proportion of food expenditure are acquired from the four categories of rubber farmers, and the sustainability of household food security is 27,08%, less is 43,75%, while the proportion of vulnerable is 12,50% and food insecurity is 6,67%. With a PPH score of 62,49, diversity is not achieved in nine food groups of rubber farmer households. Key words: food security, rubber farmer, food pattern of hope (PPH)